PENGARUH REALISASI DANA DESA TERHADAP PERTUMBUHAN EKONOMI DI INDONESIA - Ismi Nabilla Yunas; Muhammad Ilhamsyah Siregar (Fakultas Ekonomi dan Bisnis UNSYIAH, 2019)
Abstract The aim of this study is to determine the effect of the realization of village funds on economic growth in Indonesia in 2015-2017. This research uses quantitative descriptive research. The data analysis tool used in this study is linear regression analysis. Based on data from BPS seen in the last 3 years, namely the period of 2015 to 2017 in general the realization of village funds in 33 provinces throughout Indonesia has increased. This shows that there is an increase in the amount of village funds given from the Central Government to Regional Governments throughout Indonesia. The results showed that the average amount of realized village funds during 2015-2017 can be seen that the average realization per province village fund in Indonesia reached Rp75,318 trillion. The realization of village funds has a positive and significant effect on economic growth in Indonesia. The implications of this study indicate that development at the smallest level of government has a positive and important influence on economic growth. Thus, it is expected that the management and utilization of village funds can be optimized in order to have a positive effect on development.Keywords: Village Fund Allocation, Realization of Village Funds, Economic Growth